The Use of Poetry in English Learning for Islamic Junior High School Students - Muh. Iqbal Zamzami; Nabella Ardama Cherya Krenata; Wahyu Indah Mala Rohmana (JELITA, 2023)
Poetry — as one of literatures, evokes a concentrated imaginative awareness of experience or a specific emotional response through language chosen and arranged for its meaning, sound, and rhythm. This qualitative research was conducted through interviews. In addition, there are several interview questions that concern problems in the learning process, namely how to apply poetry during the English learning process, the methods used in the learning process, supporting and inhibiting factors during learning, and a place to increase students’ interest in the field of literature in the use poetry as learning material. The aim is to find out how the teacher uses poetry as learning material in English class. The results of this research, the means and facilities of English teachers to improve the application of literature in Islamic Middle Schools is to hold training that brings in. This method is a new method for memorizing English vocabulary quickly. This strategy is appropriate and in line with research conducted by Yang and Dai (2011) that most students learn English by memorizing as many vocabulary words as possible. Implementation of literature in the classroom focuses more on poetry. Poetry can improve English language skills which include four core things, namely reading, writing, listening, and speaking. Poetry also provides a lot of new knowledge, increases students emotional feelings, and the use of poetry can also arouse students’ enthusiasm.